Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Successional soil acidification links bacterial community shifts to nitrogen-cycling gene potential in a subalpine spruce chronosequence - Hangyu Bai; Bingjin Wang; Xiuling Yang; Shunzhi Xue; Wenyuan Li; Caishun Qi; Kun Ma; Dengwu Li (Applied Soil Ecology, 2026)

Rhizosphere fungal communities of four Ferula species in their native habitats in northern Xinjiang - Xiuling Wang; Gaodu Liang; Li Zhuang (Rhizosphere, 2026)

Autophagy in Aquatic Animals: A Double‐Edged Sword in Environmental Stress Response and Nutritional Mitigation Strategies - Hui Gao; Yue Liu; Xiuling Li; Wenxia Wang (Reviews in Aquaculture, 2026)
The intensification of aquaculture and global climate change expose aquatic animals to multifaceted environmental stressors, triggering diverse stress‐response cascades to mitigate cellular damage and preserve physiological homeostasis. Autophagy, an evolutionarily conserved lysosome‐dependent catabolic process that degrades damaged or redundant cellular components to maintain cellular homeostasis and physiological functions, plays a crucial role in the environmental stress response in aquatic animals. This review systematically summarizes the modulatory influence of major environmental stressors (physical, chemical, and biological) on autophagic activity in aquatic species. Overall, the regulatory network mainly centers on oxidative stress responses, mitochondrial quality control, the 5′‐adenosine monophosphate‐activated protein kinase (AMPK)/mechanistic target of rapamycin kinase complex 1 (mTORC1) signaling axis, mitogen‐activated protein kinase (MAPK) cascade, endoplasmic reticulum (ER) stress and related pathways. The dynamic equilibrium of autophagic flux dictates the cellular fate balance between adaptive survival and stress‐induced injury: physiologically moderate autophagy functions as a cytoprotective and adaptive mechanism that confers stress resilience, whereas dysregulated autophagy (either impaired flux or excessive activation) disrupts cellular homeostasis and shifts cell fate toward apoptotic death. Additionally, this review explores the potential of nutritional intervention strategies to modulate autophagic activity and alleviate stress‐induced damage in aquatic animals. Finally, key challenges and prospective research directions are proposed, providing a theoretical framework for deciphering stress resistance mechanisms in aquatic animals and advancing sustainable aquaculture practices.

Network Reconfiguration Underlies Compensatory Muscle Control Across Force Gradients: Parallel Functional Network Evidence from EEG and sEMG - Xiaoguang Liu; Pengyuan Lin; Yutong Wang; Tie Liang; Xiaodong Wang; Jun Li; Peng Xiong; Xiuling Liu (Annals of Biomedical Engineering, 2026)

Computational modeling of prefrontal-amygdala circuits links functional connectivity alterations to circuit-level mechanisms in major depression - Licong Li; Fukuan Zhang; Shuaiyang Zhang; Jinzhao Wei; Kun Wang; Bote Zheng; Jianli Yang; Xiuling Liu (Journal of Computational Neuroscience, 2026)

Synthetic microbial communities: from theoretical exploration to applied innovation - Ting Wang; Lingling Xiong; Xiaolian Shen; Jingting Sun; Qian Zhou; Kehui Xiong; Xiuling Ji (World Journal of Microbiology and Biotechnology, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

Impact of Mixing Approach and Bubble Formation on In Situ Forming Implant Properties - Xinhao Lin; Seyyed Majid Eslami; Zixuan Zhen; Hong Yuan; Eric Wilson Livingston; Ananya Aggarwal; Mia Atallah; Andre O’Reilly Beringhs; Qi Li; Qiangnan Zhang; Qin Bin; Yan Wang; et al. (Pharmaceutical Research, 2026)

Optimizing hydrogenation activation pathway in Cu-based hierarchical microspheres for sustainable nitrophenols hydrogenation with ultralow-reductant-consumption - Fengting Geng; Jiajia Cheng; Xuexin Niu; Xiaoli Wang; Hongxing Wang; Chaoyue Zhao; Ling Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Lifeng Cui; Longlong Geng (Chemical Engineering Journal, 2026)

Coordination chemistry-guided construction of hierarchical lignin-derived porous carbon with dual Lewis acid–base sites for synergistic CO2 capture - Xinxin Niu; Li Bai; Xiuling Xu; Fujun Wang; Shuai Zhu; Yixian Xue; Zhi Liu; Zhao Chen (Chemical Engineering Journal, 2026)

Temperature-dependent effects of lanthanum-modified bentonite on sediment nitrogen removal processes and the underlying microbial mechanisms - Penglong Wang; Jiehua Wang; Pingping Zhang; Zhiqiang Jiao; Xiuling Bai; Zhonghua Zhao; Jinyue Fan; Songwei Zhang; Bing Zhao; Xiubo Ren; Huidian Dou; Wenhao Bai (Water Research, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Corrosion behavior and biocompatibility of MgZnP@PDA coatings on biodegradable Zn2Cu alloy - Rui Yue; Suqin Wang; Yusong Pan; Yusheng Zuo; Xiancai Meng; Gaozhi Jia; Xiuling Lin; Run Huang; Shaoding Sheng; Lingyu Li (Chemical Engineering Journal, 2026)

Esterified starch-anthocyanin composite particles synergizing with ZnCDs to construct intelligent porous films: Long-term maintenance and real-time monitoring of shrimp freshness - Run Ji; Wentao Zhang; Lepei Wang; Xiquan Li; Xinhua Zhang; Fengxian Qin; Feiwu Li; Xiuling Zhang; Tiezhu Li (Chemical Engineering Journal, 2026)

Synergistic impact of agar microsphere surface charge on the physical and oxidative stability of Pickering emulsions - Xiuling Wang; Qin Yin; Huifen Weng; Yonghui Zhang; Xiaoyan Zhuang; Anfeng Xiao; Qiong Xiao (Carbohydrate Polymers, 2026)

Chitosan/gelatin-based film activated by Pickering emulsion of citrus essential oil stabilized by esterified starch/whey protein isolate fibrils: Application in preserving freshness of blueberry - Run Ji; Hao Guo; Xu Yang; Lepei Wang; Xiuling Zhang; Hui Zhang (Food Chemistry, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Hydrogel-confined molecular iron catalyst enables enhanced selective photoelectrochemical oxidation of glycerol to glycolaldehyde - Lu Wang; Zizhong Chen; Qi Zhao; Xiuling Jiao; Dairong Chen; Yuguo Xia (Chemical Engineering Journal, 2026)

Silica Nanoparticles Induce BV-2 Cells Autophagy Via activation of NLRP3 inflammasome and CaMKK2 Signaling Pathways - Tianxiang Liu; Mingqian Wang; Yuanyuan Zhang; Li Yang; Jia Zhang; Hongzhu Wei; Xinyue Li; Huan Pang; Jiali Li; Zhixuan Luo; Mengyue Liu; Haiying Du; et al. (Molecular Neurobiology, 2026)

A Novel Palmitoylation-Related Molecular Signature for Predicting and Therapeutically Targeting Alzheimer’s Disease - Xiuling Miao; Kaiyu Luo; Yinglei Li; Yang Zhou; Meng Wei; Ting Zhang; Yazhuo Hu; Heran Wang; Jianjun Jia (Molecular Neurobiology, 2026)

Protective effect of ginsenoside Rg3 on DBP-induced spermatogenesis injury via the Src/PI3K signaling pathway - Huan Li; Hongyan Wang; Xiaolei Xu; Li Qu; Xiuling Sun; Jing Zhang (Reproductive Toxicology, 2025)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Nocturnal near-surface ozone increases events in Beijing-Tianjin-Hebei region, China during 2018–2023 and the associated mechanisms - Xiuling Wang; Hui Zhang; Xiaochen Fei; Kai Meng; Junming Chen; Jiajia Hua; Fenglian Ma; Xiaodong Zhang; Guan Wang; Chengying Zhang (Meteorology and Atmospheric Physics, 2025)

Macro-topography and coral distribution in the Xisha Islands, South China Sea - Xiuling Zuo; Zhili Yu; Guanghua Wang; Zhengxian Duan; Zuofang Yao; Kefu Yu (Acta Oceanologica Sinica, 2025)

New interpretation of the Rb/Sr ratio of the Ili loess, northeastern Central Asia - Yanping Wang; Yougui Song; Yue Li; Hamid Gholami; Haoru Wei; Mengxiu Zeng; Xiuling Chen; Li Han (Quaternary Science Reviews, 2025)

Combined effects of microplastics and copper on antioxidant capacity, gut microbiome, and metabolomics of Pseudorasbora parva - Baicai Wang; Guoao Xie; Hailun Zhang; Yueting Zhao; Yekai Sun; Hang Yuan; Lijuan Cai; Xiuling Li; Wenxia Wang; Changwei Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Construction and characterization of Pickering emulsion stabilized by agar-phenylalanine complex microgel particles - Zizhou Chen; Xiuling Wang; MeixiLiu; Huifen Weng; Xiaoyan Zhuang; Anfeng Xiao; Qiong Xiao (Carbohydrate Polymers, 2025)

An outcome-wide analysis of maternal air pollution exposure and adverse pregnancy outcomes in intrahepatic cholestasis of pregnancy - Xueqi Li; Xiuling Zhu; Daijuan Chen; Yajie Zhao; Xixi Deng; Yongchi Zhan; Bing Guo; Tingting Xu; Xiaodong Wang (Atmospheric Environment, 2025)

Engineering resistance genes against tomato brown rugose fruit virus - Junzhu Wang; Tianxin Shen; Mengjie Song; Jiayi Fan; Yiqing Li; Toto Zen Chin; Yidan Yu; Fan Huang; Xiuling Yang; Changbao Li; Xueping Zhou; Chuanyou Li; et al. (Science China Life Sciences, 2025)

Thermally triggered surface reconstruction enables self-protective layer for enhanced charge transfer in CdIn2S4 photoelectrode - Zizhong Chen; Lu Wang; Xiuling Jiao; Yuguo Xia; Dairong Chen (Chemical Engineering Journal, 2025)

Identification of brevis radix (BRX) family genes in tomato (Solanum lycopersicum) and the function of SlBRX5 and SlBRX7 under cold stress - Xiuling Chen; Changhao Mao; Rui Lv; Hecheng Sun; Shusen Liu; Zhao Liu; Aoxue Wang (Plant Science, 2025)

Intelligent active double-layer film based on ɛ-polylysine-anthocyanin co-pigmentation effect and Zn‑carbon dot construction: Effects on pork preservation, freshness monitoring and soil microbiology - Run Ji; Shuang Song; Lepei Wang; Hao Guo; Xiuling Zhang; Wentao Zhang (Chemical Engineering Journal, 2025)

Fabrication of Ti-MOF/Ti3C2 heterojunction with boosted activity for visible light-driven photocatalytic degradation - Xianghan Cheng; Zhongmin Liu; Ruilin Wang; Yajun Guo; Wenyuan Han; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Suijun Liu; Longlong Geng (Journal of Environmental Chemical Engineering, 2025)

Defect-mediated spatial confinement of Pt single atoms on photoactive CdIn2S4 octahedrons: Synergistic carrier dynamics optimization for photocatalytic hydrogen production - Zizhong Chen; Lu Wang; Xiuling Jiao; Yuguo Xia; Dairong Chen (Chemical Engineering Journal, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Silica Nanoparticles Induce SH-SY5Y Cells Death Via PARP and Caspase Signaling Pathways - Kai Ma; Tiantian Tian; Xinyue Li; Huan Pang; Xiaofan Ning; Meng Li; Jiali Li; Zhixuan Luo; Tianxiang Liu; Mengyue Liu; Mingqian Wang; Chao Zhao; et al. (Molecular Neurobiology, 2025)

Oxygen-vacancy-rich Ni/CeO2: UiO-66-derived high-efficiency catalyst for low-temperature CO2 methanation - Yidan Li; Yahui Yang; Zhenzhen Huang; Huilin Zhou; Riying Zeng; Xiaohan Lin; Xiuling Ma; Lihua Wang; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2025)

Effects of CSTB on in vitro maturation of ovine oocytes - Ying Chen; Gulimire Abudureyimu; Jiapeng Lin; Liqin Wang; Xiuling Ma; Xiangli Wu; Yangsheng Wu (Animal Reproduction Science, 2025)

The impact of Span80 single molecule and micelle forms on the structure and performance of polyamide nanofiltration membranes - Yue Miao; Xiaowen Huo; Yingying Zhao; Xiuling Liu; Haitao Wang; Jun Li; Na Chang (Journal of Water Process Engineering, 2025)

Effects of human disturbance on the landscape pattern in the mountainous area of western Henan, China - Haoran Wang; Kaiyue Wang; Yunkai Zhou; Xiuling Bai (Journal of Environmental Management, 2025)

Application of composite biological control agent in postharvest preservation of cherry tomatoes - Fanyue Meng; Mozhen Cheng; Ziqi Zhou; Peiwen Wang; Shusen Liu; Zhao Liu; Zhengfeng Song; Xiuling Chen; Aoxue Wang (Physiological and Molecular Plant Pathology, 2025)

Ultra-stable zinc-ion hybrid capacitors empowered by hydrogel electrolyte programmed with chain-additive approach - Xiuling Dong; Xinyi Ge; Wei Chen; Shuangqing Li; Zheng Xing; Zhong-Xia Wang; Qingguo Zhang (Chemical Engineering Journal, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Constructing high-performance poly(terphenyl pyridinium) membranes through efficient acid doping and controllable crosslinking for vanadium flow batteries - Tao Ban; Yinfei Wang; Yifei Xu; Zihui Wang; Xiuling Zhu (Chemical Engineering Journal, 2025)

Long-term pollution status of microplastics in sediment of a typical mariculture area - Xiaodan Wang; Jianmin Zhao; Shuang Zhao; Xiuling Yan; Shuang Guo; Yongliang Liu; Qing Wang; Jianbai Zhang (Marine Pollution Bulletin, 2024)

Accelerating peroxymonosulfate activation over fiber-shaped Fe@Fe3C/CNF for ultrafast tetracyclines degradation: Active site synergy and mechanisms - Man Yang; Yafan Lu; Wenjuan Zhang; Long Xie; Junjie Tian; Yiliyasi Baikeli; Fang Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Mika Sillanpää; Longlong Geng (Journal of Environmental Chemical Engineering, 2024)

A Machine Learning Approach for Behavioral Recognition of Stress Levels in Mice - Hao Song; Shirley Shimin Qiu; Binghao Zhao; Xiuling Liu; Yu-Ting Tseng; Liping Wang (Neuroscience Bulletin, 2024)

Analysis of population structure and genetic diversity of Camellia tachangensis in Guizhou based on SNP markers - Dejun Huang; Suzhen Niu; Dingchen Bai; Zhifei Zhao; Caiyun Li; Xiuling Deng; Yihan Wang (Molecular Biology Reports, 2024)
Background Camellia tachangensis F. C. Zhang is a five-compartment species in the ovary of tea group plants, which represents the original germline of early differentiation of some tea group plants. Methods and results In this study, we analyzed single-nucleotide polymorphisms (SNPs) at the genome level, constructed a phylogenetic tree, analyzed the genetic diversity, and further investigated the population structure of 100 C. tachangensis accessions using the genotyping-by-sequencing (GBS) method. A total of 91,959 high-quality SNPs were obtained. Population structure analysis showed that the 100 C. tachangensis accessions clustered into three groups: YQ-1 (Village Group), YQ-2 (Forest Group) and YQ-3 (Transition Group), which was further consistent with the results of phylogenetic analysis and principal component analyses (PCA). In addition, a comparative analysis of the genetic diversity among the three populations (Forest, Village, and Transition Groups) detected the highest genetic diversity in the Transition Group and the highest differentiation between Forest and Village Groups. Conclusions C. tachangensis plants growing in the forest had different genetic backgrounds from those growing in villages. This study provides a basis for the effective protection and utilization of C. tachangensis populations and lays a foundation for future C. tachangensis breeding.

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

The effects of climate and soil depth on living and dead bacterial communities along a longitudinal gradient in Chile - Xiuling Wang; Lars Ganzert; Alexander Bartholomäus; Rahma Amen; Sizhong Yang; Carolina Merino Guzmán; Francisco Matus; Maria Fernanda Albornoz; Felipe Aburto; Rómulo Oses-Pedraza; Thomas Friedl; Dirk Wagner (Science of The Total Environment, 2024)

Ca2+/ethanol driven in-situ integration of tough, antifreezing and conductive silk fibroin/polyacrylamide hydrogels for wearable sensors and electronic skin - Guangdong Sun; Xiuling He; Haixia Chen; Jinchao Li; Yongqiang Wang (Chemical Engineering Journal, 2024)

NaCl improves the vegetable quality of Mesembryanthemum crystallinum Linn. by increasing betacyanin and nutrient contents - Yanlu Liu; Qing Liu; Xiuling Liu; Yang Zhao; Yun Liu; Baoshan Wang; Min Chen (Plant and Soil, 2024)

Multi-scale modeling to investigate the effects of transcranial magnetic stimulation on morphologically-realistic neuron with depression - Licong Li; Shuaiyang Zhang; Hongbo Wang; Fukuan Zhang; Bin Dong; Jianli Yang; Xiuling Liu (Cognitive Neurodynamics, 2024)

Phosphoric acid pre-swelling strategy constructing acid-doped fluoropoly(aryl pyridinium) membranes to enable high-performance vanadium flow batteries - Tao Ban; Zihui Wang; Yinfei Wang; Yifei Xu; Zhanpeng Jiang; Rong Zeng; Xiuling Zhu (Chemical Engineering Journal, 2024)

Detection and differentiation of seven porcine respiratory pathogens using a multiplex ligation-dependent probe amplification assay - Yingshan Zhou; Haoran Yu; Xiuling Zhao; Jianbo Ni; Shiqi Gan; Wanyu Dong; Jing Du; Xingdong Zhou; Xiaodu Wang; Houhui Song (The Veterinary Journal, 2024)

Comparative Effects of Straw and Biochar on N2O Emissions from Acidic Soils - Feier Wang; Zhilong He; Xiuling Zhang; Javed Iqbal; Muhammad Shaaban; Ronggui Hu; Shan Lin; Ziwei Yan (Journal of Soil Science and Plant Nutrition, 2024)

Variations of sediment organic phosphorus and organic carbon during the outbreak and decline of algal blooms in Lake Taihu, China - Jiehua Wang; Xiuling Bai; Wenchao Li; Pingping Zhang; Mengdi Zhang; Haoran Wang; Yingge Bai (Journal of Environmental Sciences, 2024)

Diagnosis of pulmonary tuberculosis with 3D neural network based on multi-scale attention mechanism - Shidong Zhang; Cong He; Zhenzhen Wan; Ning Shi; Bing Wang; Xiuling Liu; Dailun Hou (Medical & Biological Engineering & Computing, 2024)

Sedimentary characteristics of ion-adsorption rare earth elements and assessment of their resource reuse potential due to soil and water erosion in western Fujian - Chen Xiaowei; Chen Xiuling; Chen Zhibiao; Cai Binggui; Chen Zhiqiang; Li Yue; Chen Feiyan; Wang Yi; Fan Yifei; Liu Jie (Environmental Monitoring and Assessment, 2024)

Proteomic analysis of boar sperm with differential ability of liquid preservation at 17 °C - Chenglei Song; Zhe Zhang; Yilin Wei; Yaqing Dou; Kunlong Qi; Xiuling Li; Feng Yang; Xinjian Li; Kejun Wang; Ruimin Qiao; Xuelei Han (Theriogenology, 2024)

GABA primes defense responses against Botrytis cinerea in tomato fruit by modulating ethylene and JA signaling pathways - Meiqi Li; Xinhua Zhang; Jiaoqi Li; Maratab Ali; Yuting Wang; Xiuling Liu; Fujun Li; Xiaoan Li (Postharvest Biology and Technology, 2024)

Influence spatial behavior of surface cracks and prospects for prevention methods in shallow loess tunnels in China - Junling Qiu; Dedi Liu; Kai Zhao; Jinxing Lai; Xiuling Wang; Zhichao Wang; Tong Liu (Tunnelling and Underground Space Technology, 2024)

Maritime Search Path Planning Method of an Unmanned Surface Vehicle Based on an Improved Bug Algorithm - Xiuling Wang; Yong Yin; Qianfeng Jing (Journal of Marine Science and Engineering, 2023)
Due to the complicated and changing circumstances of the sea environment, path planning technology is essential for unmanned surface vehicles (USVs) to fulfill search tasks. In most cases, the location of the underwater target is unknown, so it is necessary to completely cover the search area. In this paper, the global static path is planned using a parallel line scan search. When encountering unknown obstacles, the improved Bug algorithm is used for local dynamic path planning according to the sensor detection information. This paper first sets up the safe expansion area to ensure the safety of the USV during the obstacle avoidance process and optimizes the movement direction considering the operation and behavior characteristics of the USV. To meet the requirement of USV steering, the Bezier curve is used to smooth the path points, which greatly improves the smoothness of the path. In this paper, the multi-mode switching strategy of the Bug algorithm based on obstacle boundary width obtained by the sensor is proposed, which ensures no area omissions and meets the requirement of search area coverage during the process of bypassing obstacles. The simulation results show that the improved Bug algorithm can maintain a safe distance along the obstacle boundary to bypass the obstacle. Moreover, the improved Bug algorithm effectively improves the path oscillation phenomenon of traditional Bug and shortens the path length and operating time. Finally, through the global search path planning simulation and comparison experiments, the effectiveness of the proposed method is verified.

Phase reconstruction of Co3O4 with enriched oxygen vacancies induced by cold plasma for boosting methanol-to-formate electro-oxidation - Jingsen Zhang; Yue Hua; Hong Li; Xiuling Zhang; Chuan Shi; Yuxiang Li; Lanbo Di; Zongyuan Wang (Chemical Engineering Journal, 2023)

Combined use of Trichoderma harzianum and Clonostachys rosea to manage Botrytis cinerea infection in tomato plants - Fengshuo Li; Hossien Ghanizadeh; Wenwei Song; Shuang Miao; Hui Wang; Xiuling Chen; Jiayin Liu; Aoxue Wang (European Journal of Plant Pathology, 2023)

Green construction of metal- and additive-free citrus peel-derived carbon dot/g-C3N4 photocatalysts for the high-performance photocatalytic decomposition of sunset yellow - Dezhuang Gong; Jialiang Guo; Fan Wang; Jing Zhang; Shuang Song; Bingxin Feng; Xiuling Zhang; Wentao Zhang (Food Chemistry, 2023)

3D Convolution neural network with multiscale spatial and temporal cues for motor imagery EEG classification - Xiuling Liu; Kaidong Wang; Fengshuang Liu; Wei Zhao; Jing Liu (Cognitive Neurodynamics, 2023)

Boosting C2+ production from photoelectrochemical CO2 reduction on gallium doped Cu2O - Xiuling Guo; Cong Wang; Zihao Yang; Yong Yang (Chemical Engineering Journal, 2023)

Impact of Apparatus and Adapter on In vitro Drug Release of Ophthalmic Semisolid Drug Products - Catheleeya Mekjaruskul; André O’Reilly Beringhs; Bin Qin; Yan Wang; Pallabita Chowdhury; Xiuling Lu (Pharmaceutical Research, 2023)

Study on metal elements in indoor particulate matter: a case study of rural residential environment in Northeast China - Chunhui Li; Li Bai; Jia Qin; Yuqi Guo; Han Wang; Xiuling Xu (Environmental Geochemistry and Health, 2023)

Facile one-pot synthesis of multifunctional tetracycline hydrochloride nanoparticles with high stability and photothermal effect for synergistically improved antibacterial performance and sustainability - Mingzhou Lu; Weitao Wang; Xiuling Fang; Yang Xuan; Liying Chen; Xiaojing Wang; Jianhao Wang; Cheng Wang (Sustainable Chemistry and Pharmacy, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

Correction to: Evaluation of salinity resistance and combining ability analysis in the seedlings of mulberry hybrids (Morus alba L.) - Xiuling Chen; Yujun Gao; Donghao Zhang; Yanxia Gao; Yongxue Song; Hui Wang; Baojun Ma; Jisheng Li (Physiology and Molecular Biology of Plants, 2023)

Effects of heavy rain on the concentrations and forms of carbon, nitrogen and phosphorus in urban rivers of northern China - Wenchao Li; Jiehua Wang; Yunkai Zhou; Pingping Zhang; Xiuling Bai (Environmental Science and Pollution Research, 2023)

Microbiome - based agents can optimize composting of agricultural wastes by modifying microbial communities - Fengshuo Li; Hossein Ghanizadeh; Guangliang Cui; Jiayin Liu; Shuang Miao; Chang Liu; Wenwei Song; Xiuling Chen; Mozhen Cheng; Peiwen Wang; Yao Zhang; Aoxue Wang (Bioresource Technology, 2023)

Evaluation of salinity resistance and combining ability analysis in the seedlings of mulberry hybrids (Morus alba L.) - Xiuling Chen; Yujun Gao; Donghao Zhang; Yanxia Gao; Yongxue Song; Hui Wang; Baojun Ma; Jisheng Li (Physiology and Molecular Biology of Plants, 2023)

Development and characterization of yeast-incorporated coating films for improving the postharvest shelf-life of snap beans - Xinmao Li; Hossein Ghanizadeh; Zhengyuan Han; Tiantian Li; Yinghui Li; Zhitao Dou; Youwen Qiu; Xiuling Chen; Yao Zhang; Jiayin Liu; Aoxue Wang (Postharvest Biology and Technology, 2023)

Estrogen upregulates DNA2 expression through the PI3K-AKT pathway in endometrial carcinoma - Xinyan Wang; Xiuling Xu; Ting Zhang; Yang Jin; Sheng Xu; Lifeng Chen; Yucheng Lai; Ling Zhang; Ruolang Pan; Yan Yu (Journal of Zhejiang University-SCIENCE B, 2023)

Comparison between diffusive gradients in thin film technology (DGT) and traditional methods for prediction of plant available heavy metals in agricultural soil - Xiuling Bai; Wenna Ye; Yunkai Zhou; Xinling Ruan; Jiehua Wang; Wenchao Li; Pingping Zhang (Journal of Soils and Sediments, 2023)

Genome-wide identification and expression analysis of the SlNAC gene family in tomato based on a high-quality genome - Xiuling Chen; Fulei Mo; Chunyang Shen; Lingjun Meng; Yuxin Zou; Xiaopeng Xue; Mozhen Cheng; Fanyue Meng; Haonan Qi; Aoxue Wang (Horticulture, Environment, and Biotechnology, 2022)

Occurrence and distribution of geminiviruses in China - Fangfang Li; Rui Qiao; Zhanqi Wang; Xiuling Yang; Xueping Zhou (Science China Life Sciences, 2022)

The impact of TOPBP1 mutations in human cancers on the DNA damage response - Zhenzhen Yan; Xiuling Ge; Jiaxu Wang; Feng Xu; Mengyao Li; Xiuhua Liu; Xiaochun Yu; Chen Wu (Genome Instability & Disease, 2022)

The Sm gene conferring resistance to gray leaf spot disease encodes an NBS-LRR (nucleotide-binding site-leucine-rich repeat) plant resistance protein in tomato - Huanhuan Yang; Hexuan Wang; Jingbin Jiang; Mingyue Liu; Zengbing Liu; Yinxiao Tan; Tingting Zhao; He Zhang; Xiuling Chen; Jingfu Li; Aoxue Wang; Minmin Du; et al. (Theoretical and Applied Genetics, 2022)

Effects of polystyrene microplastics on copper toxicity to the protozoan Euglena gracilis: emphasis on different evaluation methods, photosynthesis, and metal accumulation - Xiuling Li; Zhengjun Wang; Ming Bai; Zhehua Chen; Gan Gu; Xi Li; Changwei Hu; Xuezhen Zhang (Environmental Science and Pollution Research, 2022)

Construction of circRNA-related ceRNA networks in longissimus dorsi muscle of Queshan Black and Large White pigs - Kunlong Qi; Yingke Liu; Chenlei Li; Xinjian Li; Xiuling Li; Kejun Wang; Ruimin Qiao; Xuelei Han (Molecular Genetics and Genomics, 2022)

Molecular mapping and characterization of QBp.caas-3BL for black point resistance in wheat (Triticum aestivum L.) - Cuihe Liu; Jie Song; Siyang Liu; Jingdong Liu; Dengan Xu; Xiuling Tian; Yingjie Bian; Yachao Dong; Fengju Wang; Rongge Wang; Zhonghu He; Xianchun Xia; et al. (Theoretical and Applied Genetics, 2021)

The impact of policy mixes on new energy vehicle diffusion in China - Xiuling Liu; Fuji Xie; Haihua Wang; Chujiang Xue (Clean Technologies and Environmental Policy, 2021)

Human endogenous retrovirus W family envelope protein (HERV-W env) facilitates the production of TNF-α and IL-10 by inhibiting MyD88s in glial cells - Xiuling Wang; Xiulin Wu; Jin Huang; Haiyan Li; Qiujin Yan; Fan Zhu (Archives of Virology, 2021)

Impact of Membranes on In Vitro Release Assessment: a Case Study Using Dexamethasone - Catheleeya Mekjaruskul; André O’Reilly Beringhs; Wei-Chung Luo; Qingguo Xu; Matthew Halquist; Bin Qin; Yan Wang; Xiuling Lu (AAPS PharmSciTech, 2021)

Karst geology and mitigation measures for hazards during metro system construction in Wuhan, China - Xiuling Wang; Jinxing Lai; Siyue He; Rodney Sheldon Garnes; Yuwei Zhang (Natural Hazards, 2020)

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Soluble receptor for advanced glycation end-products promotes angiogenesis through activation of STAT3 in myocardial ischemia/reperfusion injury - Xianxian Cao; Bin Li; Xuejie Han; Xiuling Zhang; Mengqiu Dang; Hongxia Wang; Fenghe Du; Xiangjun Zeng; Caixia Guo (Apoptosis, 2020)

Exposure to copper altered the intestinal microbiota in Chinese brown frog (Rana chensinensis) - Yijie Yang; Xiuling Song; Aixia Chen; Hongyuan Wang; Lihong Chai (Environmental Science and Pollution Research, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

A cross-sectional survey based on blood VOCs, hematological parameters and urine indicators in a population in Jilin, Northeast China - Xiaocui Li; Yuanyuan Guo; Xiuling Song; Yinghua He; Huiwen Zhang; Hao Bao; Xinxin Li; Yushen Liu; Yue Zhai; Juan Wang; Kun Xu; Juan Li (Environmental Geochemistry and Health, 2019)

Adaptive growth response of exotic Elaeagnus angustifolia L. to indigenous saline soil and its beneficial effects on the soil system in the Yellow River Delta, China - Yan Qi; Junpeng Li; Chunxiao Chen; Lingxiao Li; Xiuling Zheng; Jing Liu; Tingting Zhu; Caihong Pang; Baoshan Wang; Min Chen (Trees, 2018)

Influence of Manufacturing Process Variables on the Properties of Ophthalmic Ointments of Tobramycin - Shilpa Patere; Bryan Newman; Yan Wang; Stephanie Choi; Sahil Vora; Anson W. K. Ma; Michael Jay; Xiuling Lu (Pharmaceutical Research, 2018)

Response characteristics and preventions for seismic subsidence of loess in Northwest China - Junling Qiu; Xiuling Wang; Jinxing Lai; Qian Zhang; Junbao Wang (Natural Hazards, 2018)

Correction to: The catastrophic landside in Maoxian County, Sichuan, SW China, on June 24, 2017 - Junling Qiu; Xiuling Wang; Siyue He; Houquan Liu; Jinxing Lai; Lixin Wang (Natural Hazards, 2018)

Native promoters of Corynebacterium glutamicum and its application in l-lysine production - Xiuling Shang; Xin Chai; Xuemei Lu; Yuan Li; Yun Zhang; Guoqiang Wang; Chen Zhang; Shuwen Liu; Yu Zhang; Jiyin Ma; Tingyi Wen (Biotechnology Letters, 2018)

The earthquake in Jiuzhaigou County of Northern Sichuan, China on August 8, 2017 - Hao Lei; Xiuling Wang; Hang Hou; Linjian Su; Deqiang Yu; Hao Wang (Natural Hazards, 2018)

The catastrophic landside in Maoxian County, Sichuan, SW China, on June 24, 2017 - Junling Qiu; Xiuling Wang; Siyue He; Houquan Liu; Jinxing Lai; Lixin Wang (Natural Hazards, 2017)

HBV X Protein induces overexpression of HERV-W env through NF-κB in HepG2 cells - Cong Liu; Lijuan Liu; Xiuling Wang; Youyi Liu; Miao Wang; Fan Zhu (Virus Genes, 2017)

Remediation mechanisms of mercapto-grafted palygorskite for cadmium pollutant in paddy soil - Xuefeng Liang; Xu Qin; Qingqing Huang; Rong Huang; Xiuling Yin; Yanming Cai; Lin Wang; Yuebing Sun; Yingming Xu (Environmental Science and Pollution Research, 2017)

Fine-mapping qFS07.1 controlling fiber strength in upland cotton (Gossypium hirsutum L.) - Xiaomei Fang; Xueying Liu; Xiaoqin Wang; Wenwen Wang; Dexin Liu; Jian Zhang; Dajun Liu; Zhonghua Teng; Zhaoyun Tan; Fang Liu; Fengjiao Zhang; Maochao Jiang; et al. (Theoretical and Applied Genetics, 2017)

Upregulation of hydroxysteroid sulfotransferase 2B1b promotes hepatic oval cell proliferation by modulating oxysterol-induced LXR activation in a mouse model of liver injury - Zhengyang Wang; Xiaoming Yang; Liang Chen; Xiuling Zhi; Hanyu Lu; Yanxia Ning; Joe Yeong; Sifeng Chen; Lianhua Yin; Xinhong Wang; Xiaobo Li (Archives of Toxicology, 2017)

Complete genome sequence of the cold-active bacteriophage VMY22 from Bacillus cereus - Kunhao Qin; Benxu Cheng; Shengting Zhang; Nan Wang; Yuan Fang; Qi Zhang; Anxiu Kuang; Lianbing Lin; Xiuling Ji; Yunlin Wei (Virus Genes, 2016)

Isolation and Characterization of the Lytic Cold-Active Bacteriophage MYSP06 from the Mingyong Glacier in China - Mingyuan Li; Jilian Wang; Qi Zhang; Lianbing Lin; Anxin Kuang; Luis Alberto Materon; Xiuling Ji; Yunlin Wei (Current Microbiology, 2016)

Plastid DNA insertions in plant nuclear genomes: the sites, abundance and ages, and a predicted promoter analysis - Hongyu Chen; Ying Yu; Xiuling Chen; Zhenzhu Zhang; Chao Gong; Jingfu Li; Aoxue Wang (Functional & Integrative Genomics, 2015)

Activation of elements in HERV-W family by caffeine and aspirin - Chunlan Liu; Yatang Chen; Shan Li; Honglian Yu; Jie Zeng; Xiuling Wang; Fan Zhu (Virus Genes, 2013)

Whole transcriptome analysis using next-generation sequencing of model species Setaria viridis to support C4 photosynthesis research - Jiajia Xu; Yuanyuan Li; Xiuling Ma; Jianfeng Ding; Kai Wang; Sisi Wang; Ye Tian; Hui Zhang; Xin-Guang Zhu (Plant Molecular Biology, 2013)

Ecto-5′-nucleotidase (CD73) promotes tumor angiogenesis - Li Wang; Shaoxian Tang; Yingjian Wang; Siguang Xu; Jerry Yu; Xiuling Zhi; Zhouluo Ou; Jiayin Yang; Ping Zhou; Zhimin Shao (Clinical & Experimental Metastasis, 2013)

Two natural recombinant highly pathogenic porcine reproductive and respiratory syndrome viruses with different pathogenicities - Nanhua Chen; Xiuling Yu; Lilin Wang; Jiajun Wu; Zhi Zhou; Jianqiang Ni; Xiangdong Li; Xinyan Zhai; Kegong Tian (Virus Genes, 2013)

Identification and characterization of an Apis cerana cerana Delta class glutathione S-transferase gene (AccGSTD) in response to thermal stress - Huiru Yan; Haihong Jia; Xiuling Wang; Hongru Gao; Xingqi Guo; Baohua Xu (The Science of Nature, 2013)

Physiological Characteristics and Leaf Ultrastructure of a Novel Chlorophyll-deficient chd6 Mutant of Vitis venifera Cultured in vitro - Delong Yang; Sheng Li; Mengfei Li; Xiuling Yang; Wangtian Wang; Ziyi Cao; Wei Li (Journal of Plant Growth Regulation, 2012)

Improving cooking and eating quality of Xieyou57, an elite indica hybrid rice, by marker-assisted selection of the Wx locus - Dahu Ni; Shilu Zhang; Sheng Chen; Yong Xu; Li Li; Hao Li; Zongyang Wang; Xiuling Cai; Zefu Li; Jianbo Yang (Euphytica, 2011)

Self-Assembled Hydrophobic Honokiol Loaded MPEG-PCL Diblock Copolymer Micelles - MaLing Gou; XiuLing Zheng; Ke Men; Juan Zhang; BiLan Wang; Lei Lv; XiuHong Wang; YinLan Zhao; Feng Luo; LiJuan Chen; Xia Zhao; YuQuan Wei; et al. (Pharmaceutical Research, 2009)

A self-adapting model for assessing hazardous environmental releases - Darrell W. Pepper; Xiuling Wang (Natural Hazards, 2008)

RNA interference of ecto-5′-nucleotidase (CD73) inhibits human breast cancer cell growth and invasion - Xiuling Zhi; Sifeng Chen; Ping Zhou; Zhimin Shao; Li Wang; Zhouluo Ou; Lianhua Yin (Clinical & Experimental Metastasis, 2007)

Fracture detection by using full azimuth P wave attributes - Qu Shouli; Ji Yuxin; Wang Xin; Wang Xiuling; Chen Xinrong; Shen Guoqiang (Applied Geophysics, 2007)

Heterosis in root development and differential gene expression between hybrids and their parental inbreds in wheat (Triticum aestivum L.) - Zhangkui Wang; Zhongfu Ni; Hualing Wu; Xiuling Nie; Qixin Sun (Theoretical and Applied Genetics, 2006)

Stable Inheritance of the Antisense Waxy Gene in Transgenic Rice with Reduced Amylose Level and Improved Quality - Qiaoquan Liu; Zongyang Wang; Xiuhua Chen; Xiuling Cai; Shuzhu Tang; Hengxiu Yu; Jinliu Zhang; Menming Hong; Minghong Gu (Transgenic Research, 2003)